PUNISHMENTS FOR HOMOSEXUALS IN INDONESIAN CRIMINAL POLICY PERSPECTIVE - Mohd. Din; Ali Abubakar; Azhari Yahya (Kanun Jurnal Ilmu Hukum, 2023)
The purpose of this paper is to analyze the crime of homosexuals (liwat) in the Qanun Jinayat which has been enforced in Aceh, one of the provinces in Indonesia, since 2015, especially regarding the formulation of the punishment. This topic needs to be studied considering that homosexuality in Aceh is seen as a crime that must be punished, some experts see it as a disease that needs to be cured. Therefore, the assessment needs to be linked to the purpose of punishment which is closely related to the type of crime and the method of implementation. The research was conducted using a normative juridical approach, by examining the provisions of punishment in the Qanun Jinayat which were seen from the principles and theories of the purpose of punishment and sentencing policies. The results of the study indicate that the sentencing provisions in the Qanun Jinayat are not yet integrative, so that the purpose of the sentencing has not been fully achieved. However, in several respects, the Qanun has led to both punishment and action. It is still necessary to set norms and completeness of facilities. The position of the Qanun Jinayat, especially the regulation of homosexuals, can be a pioneer in reforming criminal law in Indonesia.